2018
DOI: 10.2174/0929867325666180313112229
|View full text |Cite
|
Sign up to set email alerts
|

IAP Proteins Antagonist: An Introduction and Chemistry of Smac Mimetics under Clinical Development

Abstract: Small molecules that mimic Smac are continuously progressing towards clinical development. Smac mimetics are generally well tolerated and have demonstrated rapid suppression of their target (the IAPs), activation of apoptosis and anti-tumor activity. Continuous research has been done to generate even more insight into the function of IAP proteins to significantly enhance the therapeutical potential of Smac mimetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Several studies have shown that overexpression of SMAC/DIABLO can sensitize cancer cells to apoptosis, thus the development of small-molecule SMAC mimetics has been an attractive goal for cancer treatment in the last decade [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that overexpression of SMAC/DIABLO can sensitize cancer cells to apoptosis, thus the development of small-molecule SMAC mimetics has been an attractive goal for cancer treatment in the last decade [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…In brief, as a result of either low level or dysfunction, the activity of SMAC decreases in cancer cells, rendering it unable to antagonize the upregulated IAPs. Thus, SMs, also known as IAP antagonists, which are a new class of targeted drugs to suppress the IAPs, came into view [63].…”
Section: Depression Of Smac Activity Due To Overexpression Of Iapsmentioning
confidence: 99%
“…However, when AREL1 is present, SMAC is ubiquitylated by AREL1 and degraded, thus blocking SMAC-cIAP1/2 complex formation enabling cell survival [33]. Many cancer therapies are interested in specifically turning on apoptosis through IAPs in cancer cells [47][48][49], Figure 1. AREL1 domain architecture.…”
Section: Arel1 a Key Regulator Of Apoptosis And Potential Oncogenic mentioning
confidence: 99%